Numerical study of the mercier plasma stability and equilibrium plasma currents in an l=2 YAMATOR - Kalyuzhnyj, V.N.; Nemov, V.V. (Вопросы атомной науки и техники, 2002)
In paper [1] a new stellarator-type magnetic system having a high magnetic well value was proposed (later it got the name YAMATOR). In the present work the MHD plasma stability depending from value of the total vertical magnetic field for the magnetic configuration of l=2 variant of a similar system is investigated numerically. To investigate the plasma stability using the Mercier stability criterion, we apply the numerical method based on the calculation of the terms contained in Mercier criterion by tracing the magnetic field lines in the given stellarator magnetic field [3,4]. The magnetic field of helical windings is calculated by the Biot-Savart law. From our analysis of the MHD plasma stability in the trap under consideration it follows that the Mercier stability criterion is satisfied for a great part of the plasma-confinement region, and the violation of this criterion can take place only for the magnetic surfaces from the external part of the plasma column.